Doctor Who 50 : the essential guide - Richards, Justin (BBC Children's Books, 2013)
This essential guide to fifty years of Doctor Who includes all eleven incarnations of the Doctor and fascinating facts on his adventures in space and time, as well as his helpful companions and fearsome foes. Find out all about the Doctor's TARDIS, his regenerations, and much more.